2013
DOI: 10.1260/2040-2295.4.4.453
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamic Sensor in Cardiac Implantable Electric Devices: The Endocardial Accelaration Technology

Abstract: There have been substantial progresses in the technology of cardiac implantable electric devices (CIEDs) during the past decades. One of the progresses is represented by the development of a hemodynamic sensor embedded at the tip of a pacing lead that measures myocardial contractility by the analysis of myocardial mechanical vibrations occurring during the cardiac cycle. This sensor, providing continuous hemodynamic monitoring, could play an important role in clinical practice because of several clinical appli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…The SonR sensor records an endocardial acceleration signal corresponding to these vibrations. The highest amplitude of the signal occurs during the isovolumetric contraction phase of the cardiac cycle and corresponds to the cardiac contractility 15 . The correlation between the amplitude of the recorded signal and LV dP / dt max , as a surrogate of the contractile function of the heart, has been demonstrated 16 .…”
Section: Methodsmentioning
confidence: 95%
“…The SonR sensor records an endocardial acceleration signal corresponding to these vibrations. The highest amplitude of the signal occurs during the isovolumetric contraction phase of the cardiac cycle and corresponds to the cardiac contractility 15 . The correlation between the amplitude of the recorded signal and LV dP / dt max , as a surrogate of the contractile function of the heart, has been demonstrated 16 .…”
Section: Methodsmentioning
confidence: 95%
“…Recently introduced SonR technology uses a cardiac contractility sensor in the tip of a permanent pacing lead to endocardially measure cardiac muscle vibrations, which are directly correlated with LV dP/dt max [8][9][10]. A dedicated algorithm in certain CRT-defibrillator (CRT-D) systems (MicroPort CRM, Saluggia, Italy) uses SonR sensor metrics to implement automatic weekly optimization of AV and VV delays [11].…”
Section: Introductionmentioning
confidence: 99%
“…During the last 40 years, cardiac implantable electric devices evolved considerably and various technological aspects have been progressed (electrodes, connectors, sensors, algorithms) mainly related to the detection of cardiac arrhythmias, management of pacing/sensing thresholds, reduction of unnecessary ventricular pacing, prevention of atrial tachyarrhythmia recurrence, development of rate responsive pacing and rate adaptive atrioventricular (AV) delay functions, aimed at a better management of patients . One innovation is represented by the development of a hemodynamic sensor (SonR) incorporated at the tip of an implantable pacing lead, able to detect the acceleration of the endocardial wall of the left ventricle . SonR sensor records and amplifies myocardial vibrations during the entire cardiac cycle, transforming them into an electric signal that is processed and converted into a peak endocardial acceleration (PEA) signal .…”
Section: Introductionmentioning
confidence: 99%
“…One innovation is represented by the development of a hemodynamic sensor (SonR) incorporated at the tip of an implantable pacing lead, able to detect the acceleration of the endocardial wall of the left ventricle . SonR sensor records and amplifies myocardial vibrations during the entire cardiac cycle, transforming them into an electric signal that is processed and converted into a peak endocardial acceleration (PEA) signal . Previous studies have revealed a high correlation between PEA amplitude recorded in the right ventricle and left ventricular (LV) dP/dt max .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation